2023
DOI: 10.3390/agriculture13101936
|View full text |Cite
|
Sign up to set email alerts
|

Seed Fatty Acid Changes Germination Response to Temperature and Water Potentials in Six Sesame (Sesamum indicum L.) Cultivars: Estimating the Cardinal Temperatures

Hamidreza Balouchi,
Vida Soltani Khankahdani,
Ali Moradi
et al.

Abstract: Seed fatty acid composition can influence seed quality, followed by seed germination and optimal seedling establishment. Therefore, to find out the role of seed fatty acids in changing the cardinal temperatures of six sesame cultivars germinated at different temperatures (10, 15, 20, 25, 30, 35, 40, and 45 °C) and water potentials (0, −0.2, −0.4, −0.6, −0.8, −1, and −1.2 MPa), an experiment was conducted. The dent-like, beta, and segmented models were used to analyze the data. The results showed that different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This research underscores that the interaction effect is contingent upon factors such as cultivar type, salinity levels, temperature, and the combined influence of salinity and temperature. Sesame exhibits high polymorphism and is recognised for possessing the greatest genetic diversity among crops [19], with its diverse cultivars exhibiting variations in stress tolerance during the germination phase [1]. The unequal response of cultivars' seed germination to increasing salinity under varying temperatures supports the proposition that the Oltan cultivar likely demonstrates salt tolerance at this stage.…”
Section: Germination Percentagementioning
confidence: 96%
See 1 more Smart Citation
“…This research underscores that the interaction effect is contingent upon factors such as cultivar type, salinity levels, temperature, and the combined influence of salinity and temperature. Sesame exhibits high polymorphism and is recognised for possessing the greatest genetic diversity among crops [19], with its diverse cultivars exhibiting variations in stress tolerance during the germination phase [1]. The unequal response of cultivars' seed germination to increasing salinity under varying temperatures supports the proposition that the Oltan cultivar likely demonstrates salt tolerance at this stage.…”
Section: Germination Percentagementioning
confidence: 96%
“…Sesame (Sesamum indicum) has long held a distinguished position among oilseeds, celebrated for its culinary and nutritional value and adaptability to diverse environmental conditions [1]. As a versatile crop, sesame boasts an array of applications, from its seeds that yield high-quality oil and a rich source of protein, to the utilisation of its oilcake in animal feed [2].…”
Section: Introductionmentioning
confidence: 99%
“…In any case, the availability of varieties with a higher MUFA content is desirable. On the other hand, the high variability in oleic and linoleic acid content could be of interest for consideration in breeding programs, since different studies in other plant species have shown that increasing the level of polyunsaturated fatty acid can improve seed performance in the field at low temperatures, and seeds with higher oleic content could be more adapted to high temperatures [45,46].…”
Section: Variation Of Fatty Acid Content In Bean Seedmentioning
confidence: 99%